If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1n + 72 = 23 Reorder the terms: 72 + 1n = 23 Solving 72 + 1n = 23 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-72' to each side of the equation. 72 + -72 + 1n = 23 + -72 Combine like terms: 72 + -72 = 0 0 + 1n = 23 + -72 1n = 23 + -72 Combine like terms: 23 + -72 = -49 1n = -49 Divide each side by '1'. n = -49 Simplifying n = -49
| x-8=4x-2 | | f(-3)=-x+10 | | 15-43=3(x-1)-4 | | 121c^2-36w^2=0 | | W(6)=250*6 | | 19=p+1 | | -6+3x+8=-210 | | 8a-(-3a)= | | 2x^4+3x^3-2x^2+14x+15=0 | | 4x-8=1+7x | | q-4=69 | | -3(5+5x)=-105 | | 3d=78 | | 1/3(6y-9)=2y=13 | | -14=q3 | | 3.14*35=109.9 | | 3d=73 | | rs+4= | | 50=h+-43 | | 10x-(8/3)-4x=6x | | h=-16t^2+55t+5 | | 3x-3(2x+4)=10 | | 3.14*35= | | h/2=1.63 | | 3(10-4)/(15-3*3) | | -12+20(x)=588 | | 96/0.40 | | 5n^2=1+5n | | f-3=2 | | k/4=3 | | 4x^2+12w+9=49 | | 18x^2-66x-252=0 |